Empowering Kratom Farmers in Strengthening Functions of Family Institutions in Hulu Kapuas District - Sabran; Nahot Tua Parlindungan Sihaloho (Yayasan Ilomata, 2023)
This research focuses on empowering kratom farmers in Kapuas Hulu Regency amidst uncertainty regarding government regulations regarding legality which have an impact on the planting and buying and selling of kratom as well as decreasing the income of farming families. This was done for four main reasons: first, the need for empowerment for kratom farmers; second, strengthening institutions and improving the family economy; third, analysis of social changes due to shifts in livelihoods; and fourth, the impact of empowerment on the welfare of the kratom farming community. This research aims to answer the challenges, obstacles and empowerment models for kratom farmers in Kapuas Hulu Regency using a Social Welfare and Community Empowerment approach. Research methods include interviews with key informants, documentation, and literature study. The output of this research includes policy recommendations to local governments and publications in the nationally accredited scientific journal SINTA 3 and Simple Patent Rights.